2018
DOI: 10.14214/df.253
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dynamics of BVOC production, storage and emission in boreal Scots pine

Abstract: Plants synthesise thousands of biogenic volatile organic compounds (BVOCs) as part of their secondary metabolism. Scots pine (Pinus sylvestris) particularly produces monoand sesquiterpenes, which are mainly stored in oleoresin in resin ducts. In this study, the monoterpene emission rate from stems was found to increase as a function of increasing resin pressure, which was positively correlated with the air temperature and foliage transpiration rate.Monoterpene synthase activity describes the maximum monoterpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 99 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…Abiotic stresses may also affect the emissions from stem: when subjected to drought, total monoterpene emissions from the stem of lodgepole x jack pine hybrids increased (Lusebrink et al 2013). Including the stem BVOC emissions into the context of the whole stand BVOC emissions for the first time, Vanhatalo (2018) calculated that the unwounded stem of Scots pine (Pinus sylvestris) trees contributed approximately 2% of the total stand BVOC emissions, while the foliage made up the largest part. Although 2% is a small proportion, omitting it will cause a bias when calculating emission sums over longer periods.…”
Section: Voc Emissions From Stemmentioning
confidence: 99%
See 4 more Smart Citations
“…Abiotic stresses may also affect the emissions from stem: when subjected to drought, total monoterpene emissions from the stem of lodgepole x jack pine hybrids increased (Lusebrink et al 2013). Including the stem BVOC emissions into the context of the whole stand BVOC emissions for the first time, Vanhatalo (2018) calculated that the unwounded stem of Scots pine (Pinus sylvestris) trees contributed approximately 2% of the total stand BVOC emissions, while the foliage made up the largest part. Although 2% is a small proportion, omitting it will cause a bias when calculating emission sums over longer periods.…”
Section: Voc Emissions From Stemmentioning
confidence: 99%
“…Measurements on the short and long-term VOC emission dynamics from tree stem are quite sparse. Temperature has been reported to drive the emissions of monoterpenes and methanol from pine stem at least at a daily scale (Vanhatalo 2018;Staudt et al 2019). However, at a longer time scale the effect may be different: Staudt et al (2019) reported largest monoterpene emissions from Maritime pine (Pinus pinaster) stem during humid rather than warm days.…”
Section: Voc Emissions From Stemmentioning
confidence: 99%
See 3 more Smart Citations